Refractory status epilepticus and glutamic acid decarboxylase antibodies in adults: presentation, treatment and outcomes. Issue 1 (March 2016) - Khawaja, Ayaz M.; Vines, Brannon L.; Miller, David W.; Szaflarski, Jerzy P.; Amara, Amy W.
Abstract: Aim . Glutamic acid decarboxylase antibodies (GAD‐Abs) have been implicated in refractory epilepsy. The association with refractory status epilepticus in adults has been rarely described. We discuss our experience in managing three adult patients who presented with refractory status epilepticus associated with GAD‐Abs. Methods . Case series with retrospective chart and literature review. Results . Three patients without pre‐existing epilepsy who presented to our institution with generalized seizures between 2013 and 2014 were identified. Seizures proved refractory to first and second‐line therapies and persisted beyond 24 hours. Patient 1 was a 22‐year‐old female who had elevated serum GAD‐Ab titres at 0.49 mmol/l (normal: <0.02) and was treated with multiple immuno‐ and chemotherapies, with eventual partial seizure control. Patient 2 was a 61‐year‐old black female whose serum GAD‐Ab titre was 0.08 mmol/l. EEG showed persistent generalized periodic discharges despite maximized therapy with anticonvulsants but no immunotherapy, resulting in withdrawal of care and discharge to nursing home. Patient 3 was a 50‐year‐old black female whose serum GAD‐Ab titre was 0.08 mmol/l, and was discovered to have pulmonary sarcoidosis. Treatment with steroids and intravenous immunoglobulin resulted in seizure resolution. Conclusion . Due to the responsiveness to immunotherapy, there may be an association between GAD‐Abs and refractory seizures, including refractory status epilepticus. Causation cannot be established since GAD‐Abs may be elevated secondary to concurrent autoimmune diseases or formed de novo in response to GAD antigen exposure by neuronal injury. Based on this report and available literature, there may be a role for immuno‐ and chemotherapy in the management of refractory status epilepticus associated with GAD‐Abs.